Penerapan Pidana Adat dan Pidana KUHP Terhadap Pelaku Tindak Pidana Zina Dikaitkan Dengan Peran Kepolisian â€ ( Studi Kasus Wilayah Hukum Persukuan Domo Air Tiris dan Kapolres Kampar) - Rido i, Muhammad; ', Erdianto; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Customary law has roots strong value to the social behavior and cultural patterns. So in practice, people are more likely to use customary law to resolve the case as well as in the materials make the guidelines and norms to regulate legal relations. Indonesia, which consists of various customs very terliahat existence that customary law and traditional criminal law is still alive in their respective regions. Particularly in the Kampar Regency Tribal Domo Air Tiris customary criminal law is still in use by the public in solving the crime of adultery. To the authors interested melakaukan ilmia research as a work in the form of a thesis titled